The financial crisis: Implications for Peru and the ordinary citizen - Odar Otero, David (2012)
The current financial crisis has unleashed much controversy and a series of fears around the world. Fears regarding the true magnitude of the crisis we are experiencing and several questions that are being asked daily: will it be the same or worse than the 2008 crisis, will it have a quick solution, how will this situation affect Peru, which has a history of very good economic growth? And the question that more than one has asked: how will this affect me, an ordinary citizen, who makes a daily effort to bring bread to my house?